If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -5x = -5x + -7 + -6x Reorder the terms: -7 + -5x = -7 + -5x + -6x Combine like terms: -5x + -6x = -11x -7 + -5x = -7 + -11x Add '7' to each side of the equation. -7 + 7 + -5x = -7 + 7 + -11x Combine like terms: -7 + 7 = 0 0 + -5x = -7 + 7 + -11x -5x = -7 + 7 + -11x Combine like terms: -7 + 7 = 0 -5x = 0 + -11x -5x = -11x Solving -5x = -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -5x + 11x = -11x + 11x Combine like terms: -5x + 11x = 6x 6x = -11x + 11x Combine like terms: -11x + 11x = 0 6x = 0 Divide each side by '6'. x = 0 Simplifying x = 0
| g-5=6.03 | | (x-6)(x+7)=-2(x+12) | | 5x^2+125=180 | | 5x^2+125=360 | | -7+n=n-7 | | 5x+36=x+2x | | -10-4x=-5 | | 48-6x=-12x | | y(12x+16z)=x(12y+14z) | | 28x^2-164x=24 | | 17x-8=-25 | | -3(1-h)=-6-6n | | -1t-23=-15 | | X+5+7=11 | | -6=-24x-15 | | f(x)=ln(121sin^2x) | | y(12x+16z)=z(14x+16y) | | 2x+8x=80 | | 9y-15=-45+4y | | -2(x-8)-23=-7 | | x(12y+14z)=z(14x+16y) | | 23-x=47 | | z(14x+16y)=y(12x+16z) | | 8n-11=13+2n | | 3X^2-3X-XY+Y= | | 15+3=1513 | | x(12y+14z)=y(12x+16z) | | 7x-2=-13 | | 3(4x-7)=4x-25 | | x(12y+14z)=y(12x+16y) | | x^2+5x=110+4x | | 2(3+4x)-2=28 |